The Effectiveness of Katuk Leaf Extract (Sauropus Androgynus) on Breastmilk Production - Darmawati, Darmawati; Kamil, Hajjul; Rosmawati, Rosmawati; Rizkia, Mira; Fajri, Nova (Jurnal Keperawatan Soedirman, 2023)
Breast Milk (ASI) is a source of nutrients that are loaded with various bioactive factors. Its unique composition, breast milk is needed to prepare for optimal growth and development for babies. Plants on the leaves of katuk (Auropus Androgynus) are traditionally used by Indonesian people to increase breast milk production. The content of the katuk leaves contains almost 7% protein and up to 19% crude fiber. These leaves are rich in vitamin K and pro-vitamin A (beta-carotene), B, and C. The minerals they contain are calcium. The purpose of this study was to identify the potential of katuk leaf extract on breast milk production in experimental animals (rabbits). Katuk leaves were obtained from Aceh Besar District (Samahani, Indrapuri and Seulimun Village). They carried out the phytochemical process in the Department of Chemistry’s laboratory, FMIPA USK and the extraction process in the pharmacology laboratory of the Faculty of Veterinary Medicine, USK. The experimental animal samples, which were rabbits that had just given birth, were divided into three groups, which were 6 rabbits in the control group, 6 rabbits in the 15 mg dose group and 6 rabbits in the 30 mg dose group. An evaluation was carried out by measuring the breastmilk of rabbits on days 1, 7 and 14. The results of the study using the Generalized Linear Model test (Post Hoc Bonferroni Repeated ANOVA) showed a p-value of .001 for the three groups. It can be concluded that there was a difference in the amount of breast milk between groups in all measurements with the difference value (CI 95%) on the 1st day 0.04 (0.002-0.084), the 7th day 0.05 (0.020-0.090), and the 14th day 0.12 (0.065-0.175). Recommendations from this study are that further research can be carried out regarding the potential of katuk leaf extract to the clinical trial stage so that it is suitable for use in humans, especially postpartum women to increase breast milk productivity.